2021
DOI: 10.3390/membranes11070522
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Methods for Spongin-like Collagen Extraction from Marine Sponges (Chondrilla caribensis and Aplysina fulva): Physicochemical Properties and In Vitro Biological Analysis

Abstract: This study aimed to compare different protocols (Protocol 1: P1; Protocol 2: P2; Protocol 3: P3; Protocol 4: P4) for the extraction of spongin-like collagen (SC) from marine sponges. The SEM micrographs demonstrated a fibrillar structure for the extracts from Chondrilla caribensis and the nodular/particulate aggregates for Aplysina fulva. FTIR showed for all samples peaks similar to collagen for both species. For C. caribensis, the extracts obtained using P2, P3, and P4 protocols presented higher values of ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
(76 reference statements)
1
2
0
1
Order By: Relevance
“…FTIR was performed to confirm the chemical composition of the isolated collagens, and both samples presented a similar spectrum (Figure 2A). In fact, both FTIR spectra are in accordance with previously published C. reniformis collagen spectra and are very similar to other previously described marine collagens obtained from other sources, indicating an apparent chemical composition conservation [23,24,26,[47][48][49][50]. Curiously, C. reniformis collagen has been reported to have similar spectra to vertebrate collagen and, more specifically, to fibrillar calf skin type I collagen [24,26].…”
Section: Discussionsupporting
confidence: 89%
“…FTIR was performed to confirm the chemical composition of the isolated collagens, and both samples presented a similar spectrum (Figure 2A). In fact, both FTIR spectra are in accordance with previously published C. reniformis collagen spectra and are very similar to other previously described marine collagens obtained from other sources, indicating an apparent chemical composition conservation [23,24,26,[47][48][49][50]. Curiously, C. reniformis collagen has been reported to have similar spectra to vertebrate collagen and, more specifically, to fibrillar calf skin type I collagen [24,26].…”
Section: Discussionsupporting
confidence: 89%
“…The authors demonstrated the antioxidant potential of the compounds, which were classified as alkaloids, saponins, tannins, and flavonoids [ 20 ]. Moreover, Araujo et al [ 21 ] demonstrated the antioxidant activity in vitro of a collagenous compound extracted from the marine sponges Chondrilla caribensis .…”
Section: Introductionmentioning
confidence: 99%
“…Type I collagen, the most abundant protein in vertebrates, has been widely used as a biomaterial as it has excellent biological functions and properties. 1,2 Extracting type I collagen from mammalian tissues using acetic acid combined with pepsin has been commonly used for decades. 3 Schmitt developed methods using the enzyme pepsin and acetic acid for extracting collagen in a high yield from bovine skin 4 .…”
Section: Introductionmentioning
confidence: 99%